The Development of Learning Achievement in Health Education Subject on Self and family health care of Mathayomsuksa 4 students by using Computer-Aided Instruction - บุญมาโฮม เจษฎา; สีนาค ปราณี; วิชัยดิษฐ ศัลพงศ์ (Journal of health and health management, 2019)
The purpose of this research were to 1) compare students’ learning achievement in Health Education Subject on topic “Self and family health care” before and after learning by using Computer Assisted Instruction Lessons 2) compare students’ learning achievement with the set criterion. and 3) compare students’ learning achievement between experimental group and control group. The sample was 62 grade 10 students at Wathuaichorakhe Witthayakom School in Nakhon Pathom province, derived by multi-stage random sampling. Instruments used to collect data were 1) Computer-Aided Instruction 2) lesson plan and 3) achievement test constructed by the researcher. The statistics used for data analysis were mean, standard deviation and t-test. The results were as follows:1)Learning achievement in Health Education Subject on Self and family health care after learning by using the Computer Assisted Instruction Lesson was higher than that of before with a statistical significance at .05.2)Students’ learning achievement was higher than the set criterion at 80 %. and 3) The experimental group’s learning achievement was higher than that of that control group with a statistical significance at .05.